2009
DOI: 10.1590/s1806-37132009000300013
|View full text |Cite
|
Sign up to set email alerts
|

Coccidioidomicose pulmonar e extrapulmonar: três casos em zona endêmica no interior do Ceará

Abstract: season and limited rainfall, concentrated in a short period of time. Therefore, coccidioidomycosis presents a limited geographic distribution, and transmission is restricted to a few months of the year. (2) The fungus disseminates as arthroconidia and is inhaled together with soil dust. In Brazil, armadillo hunting is an activity that carries a significant risk for infection.Pulmonary coccidioidomycosis is typically self-limiting but can evolve to chronicity and dissemination. (3) In a small number of indi- I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…In the present study, the patients were young males (median age, 30 years), living in rural areas. The data from this study corroborate those from other published studies that indicated that this disease was predominant among males with age ranging between 19 and 43 years 3,9 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the patients were young males (median age, 30 years), living in rural areas. The data from this study corroborate those from other published studies that indicated that this disease was predominant among males with age ranging between 19 and 43 years 3,9 .…”
Section: Discussionsupporting
confidence: 91%
“…According to data, approximately 60% of coccidioidomycosis cases are symptomatic 15 . In the acute phase, the clinical presentation of coccidioidomycosis may resemble that of an acute bacterial or viral infection, based on the predominant symptoms of the disease (fever, cough, and pleuritic chest pain) 3,9,16 . In endemic regions, acute pulmonary coccididoidomycosis accounts for 29% of community-acquired penumonia 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Although fungi may not be directly influenced by precipitation, it may be affected by conditions in the environment that produce favorable conditions of growth fungus 27 . There were three cases of coccidioidomycosis in Sobral (Ceará) in a hot period 28 . Shriber et al .…”
Section: Discussionmentioning
confidence: 99%
“…Northeastern Brazil occurs as outbreaks or single cases and is often associated with hunting of wild animals (COSTA et al, 2001;CORDEIRO et al, 2009;TOGASHI et al, 2009). However, there is still little information on the clinical and pathologic characteristics of canine coccidioidomycosis in this area (WANKE et al, 1999).…”
Section: Introductionmentioning
confidence: 99%